Obtenção de um novo derivado da rutina e sua avaliação para aplicação cosmética - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The increase in life expectancy and environmental factors become precursor sources of skin aging, this has been the target of numerous studies in the cosmetic and pharmaceutical industry, seeking to increase the production of dermocosmetics from natural products, as the plant kingdom has a wide biodiversity of raw materials. Rutin is a flavonoid, of plant origin, which has many properties of interest for cosmetic application helping to prevent aging, even with numerous pharmacological activities, its effects are limited due to its low liposolubility and variable bioavailability, limiting its penetration into a biological membrane. . In view of this, the present work aimed to obtain a new derivative of rutin, with biological activities intended for cosmetic application and helping to improve the bioavailability of this molecule. The benzylated derivative of rutin was prepared by replacing the hydrogens and aromatic rings of rutin by benzylation with benzyl bromide and the product of this synthesis was coded as ACD32F2. Structural elucidation of the compound was carried out by NMR. Using the DPPH, ABTS and cellular antioxidant assays, the derivative showed a moderate antioxidant activity only in the biological system. In the in vitro glycation assay, ACD32F2 inhibited the formation of advanced glycation end products in collagen via the glyoxal pathway, with IC50 (μg / mL) equal to 2.45 ± 0.47. Regarding the proliferative activity, ACD32F2 stimulated cell proliferation and migration and increased the synthesis of collagen in fibroblasts, developing activity superior to rutin in both tests. Through the in silico study, the derivative showed an increase in skin permeation, presenting values higher than that of rutin. With regard to safety analyzes, ACD32F2 did not show cytotoxicity in human fibroblast and keratinocyte cell lines, at a concentration of 200μg / mL. In the genotoxicity assay, it did not induce genotoxic damage in fibroblasts. In the evaluation of irritation in a reconstructed skin model, ACD32F2 did not induce an irritant effect. Our study presented the obtaining of a new benzylated derivative of rutin and aspects of its efficacy and safety for application as a new cosmetic bioactive, however, further studies must be carried out to elucidate the mechanism of action involved with its potential biological activities.
Keywords: Pele - Envelhecimento; Cosméticos - Indústria; CIENCIAS DA SAUDE: FARMACIA; Rutina; Derivado; Benzilado; Envelhecimento; Cosmético